Comparison of Implant Systems Applied in the Mental Region in the Prosthetic Treatment of Atrophic Mandible: A 3D Finite Element Analysis - Hüseyin Can Tükel; Nida Geçkil (Ankara University, 2023)
Purpose This study aims to compare five implant-supported rehabilitation concepts of an edentulous mandible and determines the most biomechanically advantageous technique. Materials and methods Five models with implants in different configurations were created: All-on-4 concept (two anterior axial and two posterior distally curved implants), All-on-4v4 concept (four distal curved interforaminal implants), All-on-4W (two anterior mesial curved interforaminal implants and two posterior distally curved implants), the All-on-3 concept (one anterior axial and two posterior distally curved implants), and the treofil system (three interforaminal implants with titanium bar guide support). For this study, bone-level (4.3 × 13 mm) implants of Nobel Biocare and implants of the treofil system (5 × 13 mm) were used. Spherical loads were applied from the canine and molar regions to evaluate the tension, compression and von Mises stresses by applying 3D finite element analysis. Results Among the alternative concepts, treofil system were the most successful treatment option in biomechanical terms. On the other hand, All-on-3 concept was found to be the last method of choice. This was because of the high stresses on cortical and trabecular bones in most conditions. Conclusion The result of this study shows that the treophylline system is the most successful treatment option despite its technical details. Alternatively, classical All-on-4 and All-on-4v4 techniques are biomechanically successful treatment options.